Sintering Behavior, Microstructure, and Mechanical Properties: A Comparison among Pressureless Sintered Ultra-Refractory Carbides - Laura Silvestroni; Diletta Sciti (Advances in Materials Science and Engineering)
Nearly fully dense carbides of zirconium, hafnium, and tantalum were obtained by pressureless sintering at 1950°C with the addition of 5–20 vol% of MoSi2. Increasing the amount of sintering aid, the final density increased too, thanks to the formation of small amounts of liquid phase constituted by M-Mo-Si-O-C, where M is either Zr, Hf, or Ta. The matrices of the composites obtained with the standard procedure showed faceted squared grains; when an ultrasonication step was introduced in the powder treatment, the grains were more rounded and no exaggerated grains growth occurred. Other secondary phases observed in the microstructure were SiC and mixed silicides of the transition metals. Among the three carbides prepared by pressurless sintering, TaC-based composites had the highest mechanical properties at room temperature (strength 590 MPa, Young's modulus 480 GPa, toughness 3.8 MPa·m1/2). HfC-based materials showed the highest sinterability (in terms of final density versus amount of sintering aid) and the highest high-temperature strength (300 MPa at 1500 °C).